"Aged People are Rags": from classic positivism to the new era - Laranjeira, Carlos António (Saúde e Sociedade, 2010)
For human beings to fulfil their right to live a full and dignified life, to completely justify the quest for longevity, it must be socially possible for that greater life to be also a better one. For this to occur, something needs to change in the representations of old age, in the respect for its particularities, and in the supply of specific structures. Old age is a stage of life that has been socially devalued, being represented in a negative way. This reflects on the quality of life of older people. This reflexive essay shall explore the main cultural debates regarding old age by analysing two dichotomic ideological structures on aging and old age. The results defend the need to build positive images regarding aging in order to fight the traditional models of decline and depersonalization. Noteworthy is the complexity and heterogeneity of the phenomena being analysed, highlighting the application of new strategies in order to build a new era for old age anchored on the social paradigms of citizenship and plurality.